Integrasi Ilmu Matematika Terhadap Penguatan Profil Pelajar Rahmatan Lil’alamin dalam Implementasi Pembelajaran Tematik Integratif - Indriyani Indriyani (Universitas Negeri Malang, 2023)
Abstract: This study aims to observe the integration of mathematics to strengthen the students of Rahmatan Lil' Alamin in the implementation of integrative thematic learning. The activity carried out is to use the activity of buying and selling Social Arithmetic material for class VII using Fiqh Science. This type of research is qualitative research. The methods that researchers used in this study were observation, interviews, questionnaires and questionnaires. The triangulation technique used is the source triangulation technique and the technical triangulation technique, so that the results of the study can be drawn descriptive conclusions. The results in this study indicate that the integration of mathematics towards strengthening students of rahmatan lil 'alamin in the implementation of integrative thematic learning in learning by carrying out buying and selling activities that in Islam there are provisions and adab in the buying and selling process. The application of the attitude of ta'addub (civilized) and tawazun (balanced) already has a number of students who have run it quite well, although there are some students who are lacking in implementing it because they are still not serious in carrying out the buying and selling process and think it is just playing around. Efforts made by the teacher by providing direction and also motivation so that students are more confident and encourage students by setting a good example to be their role model.Keywords: Integration, Rahmatan Lil'Alamin Student Strengthening, Integrative Thematic LearningAbstrak: Penelitian ini bertujuan untuk mengamati integrasi ilmu matematika untuk penguatan pelajar rahmatan lil ‘alamin dalam implementasi pembelajaran tematik integratif. Kegiatan yang dilakukan adalah menggunakan kegiatan jual beli materi Aritmetika Sosial kelas VII menggunakan Ilmu Fiqih. Jenis penelitian ini adalah penelitian kualitatif. Metode yang peneliti lakukan dalam penelitian ini adalah observasi, wawancara, pemberian angket dan kuisioner. Teknik triangulasi yang dilakukan adalah teknik triangulasi sumber dan teknik triangulasi tenik, supaya hasil penelitian dapat ditarik kesimpulan secara deskriptif. Hasil dalam penelitian ini menunjukkan bahwa integrasi ilmu matematika terhadap penguatan pelajar rahmatan lil ‘alamin dalam implementasi pembelajaran tematik integratif dalam pembelajaran dengan melakukan kegiatan jual beli bahwa dalam Islam ada ketentuan dan adab dalam proses jual beli. Penerapan sikap ta’addub (berkeadaban) dan tawazun (berimbang) sudah ada beberapa siswa yang menjalankannya dengan cukup baik walaupun ada beberapa siswa yang kurang dalam menerapkannya dikarenakan masih belum serius dalam menjalankan proses jual beli dan menganggap hanya sekedar main-main. Upaya-upaya yang dilakukan guru dengan memberikan arahan dan juga motiivasi agar siswa lebih percaya diri dan memberikan semangat kepada siswa dengan memberikan contoh yang baik agar menjadi tauladan mereka.Kata kunci: Integrasi, Penguatan Pelajar Rahmatan Lil’Alamin, Pembelajaran Tematik Integratif